Easy one-pot synthesis of Zinc Ferrite@Graphitic Carbon Nitride for combined adsorption and photocatalytic degradation of enrofloxacin under visible light - Muchammad Tamyiz; Medya Fitri; Zahrotul Azizah; Nabila Asmarani; Inayah Rahma (Advances in Environmental Technology)
This study explores the development and application of an eco-friendly nanocomposite, OP-ZF@CN, for the degradation of enrofloxacin (ENR) in water. Antibiotics like ENR are persistent environmental pollutants, and conventional wastewater treatments are insufficient for their removal. Photocatalysis has emerged as a promising solution, offering a cost-effective, non-toxic, and efficient method for degrading contaminants. In this work, a heterojunction was formed between graphitic carbon nitride (g-C3N4, 2DCN) and zinc ferrite (ZnFe2O4, ZF), synthesized through a one-pot hydrothermal method. The resulting OP-ZF@CN nanocomposite combines the advantages of both components, improving photocatalytic performance by reducing the bandgap of 2DCN from 2.83 eV to 2.60 eV. Characterization using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FT-IR) confirmed the successful formation of the heterojunction, with ZF nanoparticles evenly distributed on the CN surface. The photocatalytic degradation of ENR was assessed under visible light, showing that OP-ZF@CN achieved a 99% degradation rate, significantly outperforming pure 2DCN and ZF. The enhanced performance could be attributed to the synergistic interaction between adsorption and photocatalysis, with rapid adsorption reaching equilibrium within 30 minutes. The adsorption capacity of OP-ZF@CN was found to be 62.23 mg g-1, as determined by Langmuir and Sips isotherm models. Additionally, the nanocomposite exhibited high photocatalytic efficiency, removing ENR 10 times faster than 2DCN alone. The study also demonstrated that OP-ZF@CN had a maximum adsorption capacity of 11.08 mg g-1 in a 10 mg L-1 ENR solution, significantly improving adsorption compared to pure 2DCN. These results were further supported by kinetic studies, indicating that the adsorption process followed pseudo-first-order kinetics. These findings suggest that OP-ZF@CN is a highly effective material for environmental applications, particularly in wastewater treatment for antibiotic removal, with a promising potential for large-scale use.